Features and status of miniature indigenous germplasm of cattle- Malnad Gidda - SINGH, P K; PUNDIR, R K; MANJUNATH, V K; RUDRESH, B H; GOVINDAIAH, M G (The Indian Journal of Animal Sciences, 2011)
Malnad Gidda cattle are small size animals and distributed in Malnad area of Karnataka. The population of the breed is about 7-8 lakh in Karnataka but is showing a declining trend. This breed has not been included in the list of recognized cattle breeds of India due to lack of information about the breed. A survey was undertaken in the 23 villages of 3 talukas of Shimoga district and 4 talukas of Chickmagalur district of Kamataka state. Data were collected for management, phenotypic characteristics, morpho-metric traits, production and reproductive performance on 398 animals belonging to 41 farmers. There were 5 coat colours found in these animals (black, brown, red, fawn and white, sometimes mixture of any 2) but black colour was predominant. Average body length, height at withers and chest girth were 87.04±O.65, 90.29±0.46, and l18.36±O.67 cm for cows and 86.53±1.93, 91±1.47 and 118.47±3.93 cm for adult males, respectively, indicated the small size of Malnad Gidda breed among all the known cattle breeds of India. The herd size varied from 3 to 35 animals. The average daily milk yield of elite cows was obtained as 2.11 kg. The age at first service in males, age at first calving of cows, service period, dry period and calving interval, were 38.06±1.24 months, 45.41±1.22 months, 8.38±1.03 months, 7.17±O.53 months and 17.02±O.68 months, respectively. Animals of this breed are playing a significant role in the rural livelihood of Malnad area of Karnataka in terms of draught, milk and manure. There is a need to take up systematic genetic improvement programme and sustainable measures for the conservation of population of this breed.